2021
DOI: 10.1016/j.irbm.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Methods for Non-Invasive Heart Rate Measurement on Wrist

Abstract: When evaluating general health condition on a patient, heart rate is an essential indicator as it is directly representative of the cardiac system state. Continuous measurement methods of heart rate are required for ambulatory monitoring involved in preliminary diagnostic indicators of cardiac diseases or stroke. The growing number of recent developments in wearable devices is reflective of the increasing demand in wrist-worn activity trackers for fitness and health applications. Indeed, the wrist represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 112 publications
0
9
0
Order By: Relevance
“…The literature has evidenced how continuous methods of heart rate measurement are essential for preliminary diagnostic indicators of any form of cardiovascular risk (cardiac diseases or stroke) [78,79] resulting from intense, physically demanding situations. However, multiple factors can also influence increases in heart rate (stress, anxiety, body posture) without necessarily representing any health risk.…”
Section: Physiological Informationmentioning
confidence: 99%
“…The literature has evidenced how continuous methods of heart rate measurement are essential for preliminary diagnostic indicators of any form of cardiovascular risk (cardiac diseases or stroke) [78,79] resulting from intense, physically demanding situations. However, multiple factors can also influence increases in heart rate (stress, anxiety, body posture) without necessarily representing any health risk.…”
Section: Physiological Informationmentioning
confidence: 99%
“…There are other methods of heart rate measurements, such as, for example, impedance-plethysmography, magneto-plethysmography, temperature-based methods, mechanical ballistocardiography, microwave ballistocardiography and ultrasound echocardiography. A review of these methods can be found in [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional non-invasive methods for cardiac activity measurement include electrocardiogram (ECG) and photoplethysmography (PPG). Both methods, although based on different concepts and measuring different phenomena, provide reliable results when used correctly [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…A simple plethysmographic device consists of a light source (usually red or near-infrared (NIR)) and a photodetector. The illuminated tissue is relatively transparent to NIR wavelengths and the level of absorption depends on hemoglobin, the oxygen transport protein that strongly absorbs NIR light [11], [12]. The variations in volume and photodetector response are related using the Beer-Lambert's law (1), which states that by illuminating tissue with an absorption coefficient α with a light source of intensity I0 and measuring the fraction of light received It, changes in thickness d can be assessed [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation